How supervisors provide and students react to EAL thesis supervision: Voices from Sweden and Indonesia - Nangimah, Musrifatun; Walldén, Robert (Frontiers in Education, 2023)
This study aimed to explore students’ and supervisors’ reported priorities and experiences regarding the provision and reception of feedback in English as an Additional Language thesis supervision. It involved thirty-nine participants (fourteen supervisors and twenty-five students) from one Swedish and three Indonesian universities. One-on-one semi-structured interviews were conducted and analyzed thematically using Biesta’s functions of education, Habermas’ communicative action theory, and perspectives on academic literacy. Firstly, we found that Swedish and Indonesian supervisors had different feedback provision priorities. Swedish supervisors described prioritizing content-focused feedback to facilitate students’ thesis writing socialization and subjectification. Conversely, most Indonesian supervisors expressed balancing content- and form-focused feedback for qualification functions. Some Indonesian supervisors reported focusing on socialization to the thesis writing, which, unlike the Swedish supervisor’s perspective, also included publication in scientific journals. Despite these differences, supervisors in both contexts tended to isolate academic language use from discipline-specific values and practices. Secondly, students in both contexts largely expressed an instrumental orientation to achieving their goals and were frustrated by supervisors phrasing feedback as questions. Many students expressed unfamiliarity with necessary methodologies and theoretical frameworks, which made supervisors’ feedback difficult to decode. Since only a few of the students viewed the feedback as a support for their process of learning, this study calls for a clear communication about the academic socialization intention through supervision. However, academic socialization cannot solely be the responsibility of supervisors but must be embedded in the curriculum courses.